(untitled) - The United Nations Office at Geneva (Geneva, 2008)
As an expanding multilateral platform, the United Nations Office at Geneva (UNOG) provides an indispensable infrastructure for collective action and helps to facilitate collaborative efforts with all stakeholders to confront these challenges. This Annual Report outlines UNOG’s role in the international community’s joint work towards a better future for all and provides an overview of our activities throughout 2008 in support of this objective. The Annual Report also identifies particular areas of concern and forward-looking priorities that will guide our work over the following years.
Keywords: International cooperation,International relations,International organization,Hợp tác quốc tế,Quan hệ quốc tế,Tổ chức quốc tế